Indelning av trakter inför gallring på Holmen Skog : en utvärdering av svårigheter och möjligheter - Burström, Adam (SLU/Dept. of Forest Resource Management, 2014)
A common goal in practical forest management is to maximize the yield, measured in economical terms. When a forest stand is thinned a so called inoptimality loss can arise due to non-optimal decisions. This means that the selected management schedule results in a lower net present value than the optimal one which lowers the profitability for the forest owner. Holmen Skog uses the term tract which means an aggregation of stands made before a management action. A tract should be delineated in different tract parts in connection with pre-thinning planning if there is different bearing capacity within the tract, different thinning grades should be used or if the tract contains a weaker part that should not be thinned. If this delineation is neglected and a standardized forest management is practiced over a bigger thinning area, there is a risk of non-optimal decisions. Inaccurate estimation of forest variables in the pre-thinning planning, e.g. basal area, has also been a problem at Holmen Skog´s region Örnsköldsvik. There is also a fear that the volume production capacity is not fully used. The aim of this study was to examine the planning of tracts done at Holmen Skog as today and analyze the possible consequences of insufficient tract delineation. 53 tracts where inventoried with an objective plot survey and the differences between the estimated basal area and dominant height and the planners’ judgments of these values were calculated. An examination was also done of how often tracts were delineated by the planners through a search in Holmen Skog´s tract bank. This was followed by two analyzes in Heureka PlanWise to determine how much of the inoptimality loss that can be assigned to erroneous forest data respective insufficient tract delineation. Interviews were done with employees at Holmen Skog to look into the possibilities and difficulties with tract delineation. The results show that planners overestimated the basal area with 3,4 m2/ha on average while dominant height on average was underestimated with 1,8 m. The planners judgments were aggregated around the average basal area in a typical thinning stand and the overestimation can partly be explained by the fact that the planners did not exclude weaker parts from thinning in a sufficient way. The extent of tract delineation varied also a great deal between different districts at region Örnsköldsvik. The analyzes in PlanWise showed an inoptimality loss of just over 2 % because of erroneous forest data and about 1 % due to insufficient delineation of the tract. The interview respondents had in general a positive attitude to tract delineation since the work becomes easier for the machine drivers, especially if areas without need for thinning are excluded. They also thought that tract delineation for different thinning grade and thinning form is good as long as the map over the tract is intelligible. The possibility to in practice delineate a tract in parts is mostly dependent on how much time the planners have vacant for this. They work under time pressure since every district has to reach a minimum limit according to the estimated harvest level made at the head office.